Um estudo dos livros literários inseridos no livro didático do terceiro ano do ensino fundamental. - Fabrícia Fátima de Sousa (2019)
This research is, which is in the field of Education and Language, has the object to study the literary books of the section “Reading Tips” of the textbook of the Quatro Cantos Collection / 3rd year of elementary school. Based on the studies developed by Evangelista (2001), Paulino (2009), Cademartori (2010), Belmiro (2014), Cosson (2016), and others, in a documental analysis, we tried to verify how the suggestions of literary books present in the textbook contribute to literary literacy. The development of the research aimed to highlight a specific literacy practice, studied by Paulino (2009) and Cosson (2014): literary literacy, which is understood as the process of appropriation of literature as a language, in which interaction and direct contact of the reader with literary works. The research was developed in three stages. The first one consisted of a bibliographical survey about several topics related to the research with the objective of guaranteeing the theoretical contribution necessary for its development. In the second stage, we analyze the literary books present in the section “Reading Tips”, which constitute the corpus of the research: Até as princesas soltam pum (Even the princesses fart); Histórias para brincar (Stories to play); Marcelo, marmelo, martelo e outras histórias (Marcelo, quince, hammer and other stories); O livro inclinado (The inclined book); PROIBIDO PARA MAIORES. As melhores piadas para crianças” (FORBIDDEN FOR THE GROWNUP: The best jokes for kids); and Uma aventura no quintal (An adventure in the backyard). The third stage consisted of a field work in which it was tried to verify if the proposed titles were made available in the library. Four libraries of municipal schools of Belo Horizonte were verified that adopted the didactic book coleção Quatro Cantos. From the survey of the loan files, it was verified which books are most wanted by the children. The dissertation is structured in four chapters. In the first chapter are conceptualized: children's literature; literacy in school; literary literacy; literary reading at school and literary literacy training at school. In the second, the structure and information that are propagated in the textbooks and teacher's manuals were described and analyzed. In the third chapter, the characteristics of the six literary books suggested in the "Reading Tips" section were analyzed. In the fourth chapter the book loan records of the four schools surveyed were descriptively recorded, and their analysis emphasized which books were available for borrowing by the children and which had the greatest demand. In the fifth chapter, the final considerations on the research were developed, correlating theoretical studies, analyzes of textbooks, manuals, literary books and their availabilities for loan in the libraries. The result of the research evidenced the most sought-after book by children, interrelating it with their description. From the preponderant implications of the research, it is possible to highlight the importance of the selection of textbooks whose literary suggestions are favorable to its readers and that these are available for direct contact of the children with them. And that works can be explored literally in reading activities.